Optimization on the geopolymer brick production from design and strength properties point of view - Siti Nafisah, Salleh (2014)
This study focuses on the use of fly ash (fly ash) as a key ingredient to replace ordinary Portland cement (OPC) to produce gebpolymer brick. The use of fly ash is also a great choice because it can conserve natural resources, preserve the environment and thereby reduce environmental pollution. Geopolyrner concrete is low cementations of CO2. Therefore, this study was undertaken to distinguish the workability of geopolymer bricks using different sodium silicate. There are five types of samples. The difference in this sample only as sodium silicate density 90 kg/M3, 85 kg/M3, 80 kg/m 3 , 75 kg/M3, 70 kg/m3 . Three tests were conducted in this study to obtain the engineering properties of geopolymer brick. Several tests are tests of compressive strength, porosity test and water absorption test. For the curing process, all samples will be placed in the chamber for the cure with the same conditions until the day of the test is 3 days, 28 days, 56 days. The chamber is placed in the open to make sure the chamber.is getting enough days. The results of the compression tests showed that the curing conditions have a significant effect on the heat from solar. Compression tests conducted at 3.28 and mechanical properties of the brick. 56 Keywords:Fly ash, OPC , Concrete, Workability, Curing process.